Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(1,=x\left(x^2-2x+1-y^2\right)=x\left[\left(x-1\right)^2-y^2\right]=x\left(x-y-1\right)\left(x+y-1\right)\\ 2,=\left(x+y\right)^3\\ 3,=\left(2y-z\right)\left(4x+7y\right)\\ 4,=\left(x+2\right)^2\\ 5,Sửa:x\left(x-2\right)-x+2=0\\ \Leftrightarrow\left(x-2\right)\left(x-1\right)=0\Leftrightarrow\left[{}\begin{matrix}x=1\\x=2\end{matrix}\right.\)
a) \(x-xy+y-y^2=x\left(1-y\right)+y\left(1-y\right)=\left(x+y\right)\left(1-y\right)\)
b) \(x^2-2x-y^2+1=\left(x^2-2x+1\right)-y^2=\left(x-1\right)^2-y^2=\left(x-y-1\right)\left(x+y-1\right)\)
c) \(4x^2-4xy+y^2=\left(2x\right)^2-2.2x.y+y^2=\left(2x-y\right)^2\)
d) \(9x^3-9x^2y-4x+4y=9x^2\left(x-y\right)-4\left(x-y\right)=\left(9x^2-4\right)\left(x-y\right)=\left(3x-2\right)\left(3x+2\right)\left(x-y\right)\)
e) \(x^3+2+3\left(x^3-2\right)=x^3+2+3x^3-6=4x^3-4=4\left(x^3-1\right)=4\left(x-1\right)\left(x^2+x+1\right)\)
\(1,x^2-xy-2x+2y\)
\(x\left(x-2\right)-y\left(x-2\right)\)
\(\left(x-2\right)\left(x-y\right)\)
\(2,x^2+4x+4-y^2\)
\(\left(x+2\right)^2-y^2\)
\(\left(x+2-y\right)\left(x+2+y\right)\)
\(3,x^2+x+y-y^2\)
\(\left(x-y\right)\left(x+y\right)+\left(x+y\right)\)
\(\left(x+y\right)\left(x-y+1\right)\)
\(4,x^3-x^2-4x+4\)
\(x^2\left(x-1\right)-4\left(x-1\right)\)
\(\left(x-1\right)\left(x^2-4\right)\)
\(\left(x-1\right)\left(x-2\right)\left(x+2\right)\)
\(=y\left(4x^2-4xy+y^2-49\right)\)
\(=y\left[\left(2x-y\right)^2-49\right]\)
\(=y\left(2x-y-7\right)\left(2x-y+7\right)\)
21, \(x^3-4x^2+4x=x\left(x^2-4x+4\right)=x\left(x-2\right)^2\)
22, \(15x^2y+20xy^2-25xy=5xy\left(3x+4y-5\right)\)
23, \(4x^2+8xy-3x-6y=4x\left(x+2y\right)-3\left(x+2y\right)=\left(4x-3\right)\left(x+2y\right)\)
24, \(x^3-6x^2+9x=x\left(x^2-6x+9\right)=x\left(x-3\right)^2\)
Tương tự :))
21.\(x^3-4x^2+4x\)
\(=x\left(x^2-4x+4\right)\)
\(=x\left(x-2\right)^2\)
22,\(15x^2y+20xy^2-25xy\)
\(=5xy\left(3x+4y-5\right)\)
23,\(4x^2+8xy-3x-6y\)
\(=4x\left(x+2y\right)-3\left(x+2y\right)\)
\(=\left(4x-3\right)\left(x+2y\right)\)
24\(x^3-6x^2+9x\)
\(=x\left(x^2-6x+9\right)\)
\(=x\left(x-3\right)^2\)
25,\(x^2-xy+x-y\)
\(=x\left(x-y\right)+\left(x-y\right)\)
\(=\left(x+1\right)\left(x-y\right)\)
26.\(xy-2x-y^2+2y\)
\(=x\left(x-2\right)-y\left(y-2\right)\)
\(=\left(x-y\right)\left(x-2\right)\)
27,\(x^2+x-xy-y\)
\(=\left(x^2-xy\right)+\left(x-y\right)\)
\(=x\left(x-y\right)+\left(x-y\right)\)
\(=\left(x+1\right)\left(x-y\right)\)
28,\(x^2+4x-y^2+4\)
\(=\left(x^2+4x+4\right)-y^2\)
\(=\left(x+2\right)^2-y^2\)
\(=\left(x+2-y\right)\left(x+2+y\right)\)
29.\(x^2-2xy+y^2-4\)
\(=\left(x-y\right)^2-2^2\)
\(=\left(x-y-2\right)\left(x-y+2\right)\)